2023
DOI: 10.1007/s00234-023-03190-1
|View full text |Cite
|
Sign up to set email alerts
|

Image quality of spectral brain computed tomography angiography using halved dose of iodine contrast medium

Abstract: Purpose Reduction in iodinated contrast medium (CM) dose is highly motivated. Our aim was to evaluate if a 50% reduction of CM, while preserving image quality, is possible in brain CT angiography (CTA) using virtual monoenergetic images (VMI) on spectral CT. As a secondary aim, we evaluated if VMI can salvage examinations with suboptimal CM timing. Methods Consecutive patients older than 18 years without intracranial stenosis/occlusion were included. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The optimal keV of VMI was determined based on the overall image quality, including objective and subjective evaluation ( 19 , 36 , 37 ). Neuhaus et al ( 19 ) found that VMIs reconstructed from cerebral CTA at 40 to 45 keV obtained optimal image quality.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal keV of VMI was determined based on the overall image quality, including objective and subjective evaluation ( 19 , 36 , 37 ). Neuhaus et al ( 19 ) found that VMIs reconstructed from cerebral CTA at 40 to 45 keV obtained optimal image quality.…”
Section: Discussionmentioning
confidence: 99%

Equipos multienergía y contraste yodado

Villanueva Campos,
Canales Lachén,
Suevos Ballesteros
et al. 2024
Radiología